2021
DOI: 10.3390/antiox11010015
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanistic Pathways Targeted by Natural Antioxidants in the Prevention and Treatment of Chronic Kidney Disease

Abstract: Chronic kidney disease (CKD) is the progressive loss of renal function and the leading cause of end-stage renal disease (ESRD). Despite optimal therapy, many patients progress to ESRD and require dialysis or transplantation. The pathogenesis of CKD involves inflammation, kidney fibrosis, and blunted renal cellular antioxidant capacity. In this review, we have focused on in vitro and in vivo experimental and clinical studies undertaken to investigate the mechanistic pathways by which these compounds exert their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 251 publications
(262 reference statements)
0
10
0
Order By: Relevance
“…Animal studies have shown that cisplatin nephrotoxicity is alleviated by administration of various antioxidants, such as coenzyme Q10 [ 26 ], vitamin C [ 27 ], vitamin E [ 28 ], resveratrol [ 29 ], and melatonin [ 30 ], suggesting that oxidative stress is also an important mechanism of cisplatin nephrotoxicity. Importantly, various natural compounds have antioxidative activity [ 31 , 32 ]. Antioxidative effect of oridonin has also been reported in several studies [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have shown that cisplatin nephrotoxicity is alleviated by administration of various antioxidants, such as coenzyme Q10 [ 26 ], vitamin C [ 27 ], vitamin E [ 28 ], resveratrol [ 29 ], and melatonin [ 30 ], suggesting that oxidative stress is also an important mechanism of cisplatin nephrotoxicity. Importantly, various natural compounds have antioxidative activity [ 31 , 32 ]. Antioxidative effect of oridonin has also been reported in several studies [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic kidney disease (CKD) is one of the fastest-growing causes of death worldwide, with progressive loss of kidney function leading to end-stage renal disease (ESRD) [ 1 ]. Fibrosis is considered the ultimate common pathway leading to ESRD [ 2 ]. The pathogenesis of renal fibrosis is characterized by glomerulosclerosis, fibrosis of the tubular interstitium and blood vessels, and scar formation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, almost 80% of patients with diabetes whose course of disease exceeds 10 years are diagnosed with DR, and their visual quality gradually decreases with time [11] . Similar to the pathogenesis of DR caused by diabetes, DN is also considered to be a microvascular disease caused by diabetes, and its most characteristic feature is the formation of diabetes glomerulosclerosis [12,13] . Moreover, approximately 25% of diabetic patients have renal complications, which have become the primary cause of end-stage renal disease (ESRD) in developed countries [14] .…”
Section: Introductionmentioning
confidence: 99%